2009
DOI: 10.1177/145749690909800308
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Length of the Care Episode after Hip Fracture: Does the Type of Fracture Matter?

Abstract: The causes for differences in LOS between fracture types were most likely due to the different surgical methods and rehabilitation practices for the fracture types. As national guidelines suggest similar rehabilitation for all hip fracture patients, there is a need for early and aggressive rehabilitation of patients with extracapsular fractures, including full-weight bearing for all but selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
4
26
0
1
Order By: Relevance
“…Data on the associations between HF type and short-term outcomes are sparse and inconsistent, though some previous reports found a longer LOS [29,30] and higher mortality in trochanteric HF [7,15,17,34]. Our results are in line with observations that HF type is not an independent prognostic factor [43,49] and is not associated with LOS [15].…”
Section: Discussionsupporting
confidence: 90%
“…Data on the associations between HF type and short-term outcomes are sparse and inconsistent, though some previous reports found a longer LOS [29,30] and higher mortality in trochanteric HF [7,15,17,34]. Our results are in line with observations that HF type is not an independent prognostic factor [43,49] and is not associated with LOS [15].…”
Section: Discussionsupporting
confidence: 90%
“…Equally wide utilisation differences have been reported in other contemporary studies, in which total hospital stay ranged from 17 to 48 days, 1,24 rates of referral to rehabilitation ranged from 21% to 67% 8,11 and mean duration of hospital-based rehabilitation was between 1 and 6 weeks. 24,25 A recent Australian study found significant differences between four states in terms of LOS for rehabilitation of specific classes of lower limb amputees.…”
Section: Discussionmentioning
confidence: 70%
“…[1][2][3] Comparisons of duration and content of hospital management at national, regional and facility levels show wide diversity. 1,4,5 Across the world, duration of hospital stay for hip fracture ranges from as little as 5 days 6 to more than 6 weeks. 1 regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the anomaly in the shapes of the length of stay distribution between intra-and extracapsular fractures, were missed with the Weibull mixture. Actually the anomaly detected by the MLP model was clinically interesting, and a more careful investigation on the issue has been reported elsewhere [48]. In brief, the rehabilitation of patients with extracapsular fractures took longer than in the intracapsular group.…”
Section: Discussionmentioning
confidence: 79%